Community concerns in the sustainable development for Lake Fundudzi Rehabilitation Project - Sehlapelo, Desiree Lorraine Mosima (My University, 2014)
This study investigates the role of the community in participating in the development and rehabilitation of Lake Fundudzi. The premise of the study is that community is the cornerstone of the success of any development. Conserving the environment is not the only way of ensuring its heritage or managing its resources. The study specifically looks at the way the community interacts with its immediate environment, namely, the lake. It examines the types of benefits available to them. Chapter One introduces the problem statement, delimitations of the study, and significance of the study. Chapter Two reviews the extant literature, proffers an overview on what a wetland is, its function; it also provides different perspectives on Sustainable Development, including international and the local perspectives applicable to South Africa and the local area. Chapter Three proffers Research Design and Methodology i.e. Observations of stakeholders, and questionnaire as a research tool. Chapter Four presents research findings of the research done in the three villages. Chapter Five analyses and interprets the research findings. Finally, Chapter Six recommends and concludes the study.
Thesis (M.M.)--University of the Witwatersrand, Faculty of Commerce, Law and Management, 2006.
Keywords: Sustainable development--Limpopo; Community development--Limpopo